2011
DOI: 10.1161/circulationaha.110.976936
|View full text |Cite
|
Sign up to set email alerts
|

Familial Evaluation in Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: Background-With recognition of disease-causing genes in arrhythmogenic right ventricular cardiomyopathy, mutation analysis is being applied. Methods and Results-The role of genotyping in familial assessment for arrhythmogenic right ventricular cardiomyopathy was investigated, including the prevalence of mutations in known causal genes, the penetrance and expressivity in genotyped families, and the utility of the 2010 Task Force criteria in clinical diagnosis. Clinical and molecular genetic evaluation was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
183
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(193 citation statements)
references
References 18 publications
(33 reference statements)
3
183
0
7
Order By: Relevance
“…Quarta et al found that relatives harbouring more than one genetic variant had a significantly increased risk of developing ARVC, an important factor when interpreting the variable expression of disease within families. This study also highlighted that penetrance may be definition-dependent, being greater with the 2010 task force criteria compared to the 1994 criteria in the case of ARVC [44].…”
Section: Developments In Genotype Phenotype Correlationmentioning
confidence: 86%
“…Quarta et al found that relatives harbouring more than one genetic variant had a significantly increased risk of developing ARVC, an important factor when interpreting the variable expression of disease within families. This study also highlighted that penetrance may be definition-dependent, being greater with the 2010 task force criteria compared to the 1994 criteria in the case of ARVC [44].…”
Section: Developments In Genotype Phenotype Correlationmentioning
confidence: 86%
“…[6][7][8][9][10][11] Our first patient had his genetic screening for mutations of desmosomal proteins, also his father had the same diagnosis, and the third patient had a family history of ARVD/C, and his elder brother managed by medical therapy.…”
Section: Discussionmentioning
confidence: 98%
“…The second phase symptomatic arrhythmias of RV origin are common and more prominent; the third phase the isolated RV failure and concomitant dysplastic process becomes diffuse with greater dilatation and dysfunction of RV and finally the fourth phase is left ventricular involvement and biventricular failure. [7][8][9][10][11] All three patients had admitted our hospital with either third phase and fourth phase. The presence of biventricular heart failure and intracardiac thrombus formation were identified as high risk group for our patients.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,[16][17][18][19] Frameshift and nonsense mutations account for 35% (79 out of 224) of PKP2 genetic alterations identified in ARVC patients (ARVD/ C Genetic Variants database; http://www.arvcdatabase.info/).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] In a unique systematic study, applying Multiplex Ligationdependent Probe Amplification (MLPA) on 169 Dutch ARVC patients, large copy number variants involving PKP2 gene were detected in three (1,8%) cases. 19 Very recently, a deletion of the entire coding region of PKP2 gene (excluding exon 1) and a 7.9 Mb deletion of chromosome 12p12.1-p11.1 encompassing PKP2 exons 1-14 were identified in two ARVC cases, by chromosomal oligo-array analysis and/or MLPA.…”
Section: Introductionmentioning
confidence: 99%